Voltage Profile Improvement of Distribution System using Distributed Generating Units - Gummadi Srinivasa Rao; Y.P Obulesh (International Journal of Electrical and Computer Engineering (IJECE), 2013)
The power system utilities are increasing everyday,to enhance the distribution power quality and maintains the voltage stability is a challenging tasks in the complex distribution This can be achieved through the Distributed Generation (DG).DGs are the final link between the high voltage transmission and the consumers,it is also known as Active Distribution networks(ADN).This will effectively improve the acive power loss reduction This paper represents technique to minimize power losses in a distribution feeder by optimizing DG model in terms of size, location and operating point of DG. Sensitivity analysis for power losses in terms of DG size and DG operating point has been performed. The proposed sensitivity indices can indicate the changes in power losses with respect to DG current injection. The proposed technique has been developed with considering load characteristics and representing constant current model. The effectiveness of the proposed technique is tested and verified using MATLAB software on long radial distribution system.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2133